KANDUNGAN PEMBICARAAN AL-QUR’AN - Hasiolan Nasution (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This article aims to look at the contents of the holy book Al-Qur'an in general. Even though the Qur'an talks about many things, it can be categorized into several big themes. Understanding the content of the Koran is important because the Koran is not only a guide for the lives of Muslims but also for mankind. This article uses a descriptive qualitative method. Data was collected from library data in the form of books, journals and related documents. It can be concluded in general that the content of the discussion in the holy Qur'an has at least seven points which include: creed, worship, promises and threats, morals, law, stories, and science and technology.